Baseline extended zone retinal vascular calibres associate with sensory nerve abnormalities in adolescents with type 1 diabetes: A prospective longitudinal study. Issue 11 (6th August 2021) - Velayutham, Vallimayil; Benitez‐Aguirre, Paul Z.; Liew, Gerald; Wong, Tien Y.; Jenkins, Alicia J.; Craig, Maria E.; Donaghue, Kim C.
Abstract: Objective: The relationship between retinal vascular calibres (RVCs) and diabetic neuropathy is unclear. We investigated associations between RVCs and sensory nerve abnormality in adolescents with type 1 diabetes. Research design and methods: In a prospective longitudinal study of 889 adolescents with type 1 diabetes with baseline mean (±SD) age 14.1 ± 1.5 years and HbA1c IFCC 69.4 ± 14.1 mmol/mol (8.6 ± 1.3%), RVCs were assessed from baseline retinal photographs: 'central zone' calibres, summarized as central retinal arteriolar (CRAE) and venular equivalents (CRVE) and 'extended zone' calibres: mean width of arterioles (MWa) and venules (MWv). Sensory nerve abnormality was defined as at least one abnormal sensory quantitative testing from two thermal and two vibration threshold tests measured at foot every 1–2 years. Associations between baseline RVC and sensory nerve function were examined using generalized estimating equations and cumulative risk by Cox regression analyses. Results: During a median study follow‐up of 6.2 [IQR 3.7–10.4] years, sensory nerve abnormality was found in 27% of adolescents. Narrower extended zone calibre quartiles but not CRAE or CRVE quartiles were independently associated with sensory nerve abnormality: MWa (Q1 vs. Q2‐4: OR 1.35 (95% CI 1.02, 1.61) and MWv (Q1 vs. Q2‐4: 1.31 (1.03, 1.7)), after adjusting for HbA1c, duration and blood pressure. Similarly, in Cox regression, the narrowest quartiles were associated with sensory nerve abnormality: MWa hazard ratio (HR) 1.5 (1.3, 1.8) and MWv 1.6 (1.4, 1.9). Conclusions: Narrower extended zone retinal calibres were associated with sensory nerve abnormality in adolescents with type 1 diabetes and may present useful biomarkers to understand the pathophysiology of neuropathy.